2008
DOI: 10.4049/jimmunol.180.4.2553
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic Acid Isolated from Lactobacillus plantarum Inhibits Lipopolysaccharide-Induced TNF-α Production in THP-1 Cells and Endotoxin Shock in Mice

Abstract: In this study, the effect of Lactobacillus plantarum lipoteichoic acid (pLTA) on LPS-induced MAPK activation, NF-κB activation, and the expression of TNF-α and IL-1R-associated kinase M (IRAK-M) was examined. The expression of the pattern recognition receptor and the survival rate of mice were also examined. pLTA pretreatment inhibited the phosphorylation of ERK, JNK, and p38 kinase. It also inhibited the degradation of IκBα and IκBβ, as well as the activation of the LPS-induced TNF-α factor in response to sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 36 publications
4
108
0
Order By: Relevance
“…The immunostimulatory activity of aLTA was remarkably diminished by removal of the fatty acid acyl group of LTA (Ohshima et al, 1988). We also demonstrated that the acyl group of pLTA was responsible for inhibiting LPS-induced TNF-a production, not the D-alanine substituent in the phosphoglycerol moiety of pLTA (Kim et al, 2008a). Based on the glycolipid analysis conducted in a previous study, the glycolipid moiety of pLTA contains unsaturated fatty acids and a third acyl chain on the conserved trihexosyldiacyl ceramide structure.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The immunostimulatory activity of aLTA was remarkably diminished by removal of the fatty acid acyl group of LTA (Ohshima et al, 1988). We also demonstrated that the acyl group of pLTA was responsible for inhibiting LPS-induced TNF-a production, not the D-alanine substituent in the phosphoglycerol moiety of pLTA (Kim et al, 2008a). Based on the glycolipid analysis conducted in a previous study, the glycolipid moiety of pLTA contains unsaturated fatty acids and a third acyl chain on the conserved trihexosyldiacyl ceramide structure.…”
Section: Discussionmentioning
confidence: 58%
“…In a previous study, we have shown that pLTA inhibited LPS-or aLTA-induced TNF-α production in THP-1 cells (Kim et al, 2008a;2008b). In addition, pLTA has low immune activation effects while LPS and aLTA induce high levels of TNF-α production.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations